The Degree of Acquiring E-Learning Competencies by English Language Teachers from The Perspective of Government School Principals at Ajloun Governorate - Jaddullah, Asmahan Hanna Rezkellah (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the degree of acquiring the e-learning competencies by English language teachers from the perspective of government school principals at Ajloun Governorate. To achieve the objectives of the study, the researcher used the descriptive analysis approach, and a questionnaire for data collection; it consisted of (25) statements that were applied to the Sample of (130) principals. The results indicated that the degree of acquiring e-learning competencies by English language teachers from the perspective of government school principals at Ajloun Governorate was "high" with a mean of (4.35). Furthermore, there were statistical significant differences at (α ≤ 0.05) in the variable of educational level (primary and secondary) in favor of the secondary one. However, there were statistically significant differences due to the years of experience of the participants in favor of (10 years and more). The study ends with some recommendations; the most important one was conducting training courses for the English teachers to keep pace with the technological developments.